2022
DOI: 10.1186/s12872-022-02711-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a circulating microRNAs biomarker panel for non-invasive diagnosis of coronary artery disease: case–control study

Abstract: Background Circulating microRNAs (miRNAs) are considered a hot spot of research that can be employed for monitoring and/or diagnostic purposes in coronary artery disease (CAD). Since different disease features might be reflected on altered profiles or plasma miRNAs concentrations, a combination of miRNAs can provide more reliable non-invasive biomarkers for CAD. Subjects and methods We investigated a panel of 14-miRNAs selected using bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 108 publications
(83 reference statements)
0
11
0
1
Order By: Relevance
“…miR-133a-3p affects the progression of atherosclerosis ( Libby et al, 2019 ), cardiac remodeling ( Li et al, 2018 ), myocardial infarction ( Paiva and Agbulut, 2017 ), ischemia-reperfusion injury ( Ye et al, 2011 ). Several studies have demonstrated that miR-133a-3p, which is considered as a candidate marker, is markedly downregulated in obesity and cardiovascular disease ( Kim et al, 2020 ; Abdallah et al, 2022 ). However, the specific role and mechanism of miR-133a-3p in atherosclerosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…miR-133a-3p affects the progression of atherosclerosis ( Libby et al, 2019 ), cardiac remodeling ( Li et al, 2018 ), myocardial infarction ( Paiva and Agbulut, 2017 ), ischemia-reperfusion injury ( Ye et al, 2011 ). Several studies have demonstrated that miR-133a-3p, which is considered as a candidate marker, is markedly downregulated in obesity and cardiovascular disease ( Kim et al, 2020 ; Abdallah et al, 2022 ). However, the specific role and mechanism of miR-133a-3p in atherosclerosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the relationship between miRNA146a rs2910164 polymorphism and different diseases such as auto‐immune, cancer, and CVDs. [ 17 ] miR‐146a is implicated in both inflammation and lipid homeostasis, [ 18,19 ] and functions by its inhibitory effect on oxidized low‐density lipoproteins and inflammatory response, [ 19 ] thus affecting the pathogenesis of atherosclerosis. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the relationship between miRNA146a rs2910164 polymorphism and different diseases such as autoimmune, cancer, and CVDs. [17] miR-146a is implicated in both inflammation and lipid homeostasis, [18,19] and functions by its inhibitory effect on oxidized low-density lipoproteins and inflammatory response, [19] thus affecting the pathogenesis of atherosclerosis. [20] miR-4513 is a latterly identified miRNA, whose polymorphisms in the seed sequence are frequently combined with fasting glucose, LDL-cholesterol and total cholesterol, systolic and diastolic blood pressure, and human diseases such as CHD and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have unveiled the potentially important function of miRNA-126-5p in vascular diseases, including atherosclerosis, coronary artery disease, stroke, and diabetic vasculopathy. The action of miRNA-126-5p reflects its function in angiogenesis and inflammation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%